2000
DOI: 10.1097/00006199-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Smoking Relapse In Postpartum Women

Abstract: Smoking cessation interventions focusing on the prenatal period have failed to achieve long-term abstinence. Interventions can be strengthened if they are extended into the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 30 publications
7
71
0
1
Order By: Relevance
“…The items are scaled from 1 (never) to 4 (always), with higher scores indicating more happiness. The composite scale of these four items has demonstrated acceptable internal consistency (Johnson et al, 2000). In the current study, the Cronbach's alpha was .75.…”
Section: Other Study Variablesmentioning
confidence: 50%
“…The items are scaled from 1 (never) to 4 (always), with higher scores indicating more happiness. The composite scale of these four items has demonstrated acceptable internal consistency (Johnson et al, 2000). In the current study, the Cronbach's alpha was .75.…”
Section: Other Study Variablesmentioning
confidence: 50%
“…Breast-feeding and mental health were protective factors, whereas partners who smoked and the greater amount smoked before pregnancy had adverse effects. 18,48 One intervention referred women to individual behavior change counseling during prenatal care in addition to standard cessation counseling from her physician. Although additional cessation counseling did not yield significantly lowered relapse rates, researchers found that greater proportions of the intervention group reported either not smoking or reducing their consumption by 50% or more.…”
Section: Interventions That Maintain Smoking Cessation During Pregnancymentioning
confidence: 99%
“…34,41 Interventions that involve the woman's partner 34,41 need further exploration. Some researchers propose extending smoking cessation programs into the postpartum period 12,18,34 or as a part of well-baby care. 11 The effects, costs, and outcomes of program extension have implications for developing a theoretic model of postpartum relapse and maintenance and for planning and implementing effective interventions.…”
Section: Further Research and Recommendationsmentioning
confidence: 99%
“…632 after 1 year in the control vs. intervention group, respectively. 28,29 This variability in smoking and cessation rates may be accounted for in part by different smoking policies in the different countries. In Germany, tobacco control activities are only just developing and are met with intense lobbying activities on behalf of the tobacco industry.…”
Section: Introductionmentioning
confidence: 99%